2011
DOI: 10.1111/j.1440-1746.2011.06786.x
|View full text |Cite
|
Sign up to set email alerts
|

Which should go first during same‐day bidirectional endosocopy with propofol sedation?

Abstract: The optimal sequence for same-day bidirectional endoscopy is EGD followed by colonoscopy. In this order, the procedure is better tolerated, and patients require a lower overall dose of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…Internationally, sedation for colonoscopy varied widely and nearly 30% colonoscopic procedure received deep sedation [31]. In Taiwan, most of patients and endoscopists favored deep sedation for the endoscopic procedures despite greater use of resource, monitoring and anesthetist [12,13]. Further worldwide observation is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, sedation for colonoscopy varied widely and nearly 30% colonoscopic procedure received deep sedation [31]. In Taiwan, most of patients and endoscopists favored deep sedation for the endoscopic procedures despite greater use of resource, monitoring and anesthetist [12,13]. Further worldwide observation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deep sedation rather than moderate sedation for endoscopy was preferred by most of the patients undergoing diagnostic colonoscopy for health check-up in Taiwan [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent US study based on a national endoscopic database showed that over 11 % of subjects had received same-day bidirectional endoscopy [2]. Of the procedures, EGD is usually performed before colonoscopy due to its superior tolerability and the lower dose of sedatives needed [3]. Now, we have another reason to perform EGD before colonoscopy-to deliver the bowel preparation regimen.…”
mentioning
confidence: 99%
“…Hsieh et al . reported that lower propofol doses were needed when a same‐day BDE procedure started with the EGD (124.7 vs 135.7 mg for EGD‐colonoscopy and colonoscopy‐EGD groups, respectively, P = 0.024) . However, in another same‐day BDE study using moderate sedation with meperidine and midazolam, Carter et al .…”
Section: Discussionmentioning
confidence: 96%
“…Two studies showed that EGD was perceived to be more stressful to patients when preceded by colonoscopy in unsedated patients . Three other studies, using moderate or deep sedation for BDE, showed that EGD followed by colonoscopy was superior in terms of better EGD tolerability and lower sedative dosages . However, a recent study with moderate sedation found that there was no difference in patient discomfort and satisfaction regarding the procedure sequence .…”
Section: Introductionmentioning
confidence: 99%